2005
DOI: 10.1097/01.icl.0000165286.05080.23
|View full text |Cite
|
Sign up to set email alerts
|

Morphometry of Cells and Guttae in Subjects With Normal or Guttate Endothelium With a Contour Detection Algorithm

Abstract: This detection algorithm is repeatable and reproducible, and it generates a cell border overlay useful in analyzing the morphology of cells and guttae. The analysis of corneal guttae could become a useful follow-up procedure to discriminate between patients with corneal guttata and Fuchs dystrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
9
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
1
9
0
1
Order By: Relevance
“…The outcome of the present study is slightly smaller (with the SD about the group mean estimate being 3.2 per cent) but not much different, although it is a comparison of two independent assessments of 100 cells from the same images using different instruments. The result is consistent with those from several other recent studies, where similar discrepancies in COV data have been reported 13,14,25 . The discrepancy is not so much in the mean value of COV obtained by comparing two instruments or a repeated analysis on a single instrument by the same operator but in the size of the range of the difference in the COV values.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The outcome of the present study is slightly smaller (with the SD about the group mean estimate being 3.2 per cent) but not much different, although it is a comparison of two independent assessments of 100 cells from the same images using different instruments. The result is consistent with those from several other recent studies, where similar discrepancies in COV data have been reported 13,14,25 . The discrepancy is not so much in the mean value of COV obtained by comparing two instruments or a repeated analysis on a single instrument by the same operator but in the size of the range of the difference in the COV values.…”
Section: Discussionsupporting
confidence: 92%
“…Such an assessment can be made by comparing the image to a set of reference grids or by actually counting the number of cells included within a specified region of interest (ROI), that is, a manual count of endothelial cell density. With the introduction of newer instruments over the past decade or so, there have been numerous comparisons made to determine the accuracy and/or reliability (repeatability) of various image analysis software systems that could replace a manual counting of the endothelial cells to provide an estimates of the ECD for a patient at a particular assessment 4–30 . Overall, most systems seem to provide reasonable estimates of ECD both when inter‐instrument and/or inter‐operator differences are taken into account.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations